Intelligent Tools for Building a Scientific Information Platform Advanced Architectures and Solutions - Bembenik, Robert; Skonieczny, Lukasz; Rybinski, Henryk; Kryszkiewicz, Marzena; Niezgodka, Marek (Studies in Computational Intelligence, 2013)
This book is a selection of results obtained within two years of research per- formed under SYNAT - a nation-wide scientific project aiming at creating an infrastructure for scientific content storage and sharing for academia, education and open knowledge society in Poland. The selection refers to the research in artificial intelligence, knowledge discovery and data mining, information retrieval and natural language processing, addressing the problems of implementing intelligent tools for building a scientific information platform.This book is a continuation and extension of the ideas presented in "Intelligent Tools for Building a Scientific Information Platform" published as volume 390 in the same series in 2012. It is based on the SYNAT 2012 Workshop held in Warsaw. The papers included in this volume present an overview and insight into information retrieval, repository systems, text processing, ontology-based systems, text mining, multimedia data processing and advanced software engineering.  .